Spatiotemporal Changes and Trade-Offs/Synergies of Ecosystem Services in the Qin-Mang River Basin - Jiwei Zhao; Luyao Wang; Dong Jia; Yaowen Wang (ISPRS International Journal of Geo-Information)
The Qin-Mang River Basin is an important biodiversity conservation area in the Yellow River Basin. Studying the spatiotemporal changes in its ecosystem services (ESs) and the trade-offs and synergies (TOSs) between them is crucial for regional ecological protection and high-quality development. This study, based on land use type (LUT), and meteorological and soil data from 1992 to 2022, combined with the InVEST model, correlation analysis, and spatial autocorrelation analysis, explores the impacts of land use/land cover changes (LUCCs) on ESs. The results show that: (1) driven by urbanization and economic development, the expansion of built-up areas has replaced cultivated land and forests, with 35,000 hectares of farmland lost, thereby increasing pressure on ESs; (2) ESs show an overall downward trend, habitat quality (HQ) has deteriorated, carbon storage (CS) remains stable but the area of low CS has expanded, and sediment delivery ratio (SDR) and water yield (WY) fluctuate due to human activities and climate influence; (3) the TOSs of ESs change dynamically, with strong synergies among HQ, CS, and SDR. However, in areas with water scarcity, the negative correlation between HQ and WY has strengthened; (4) spatial autocorrelation analysis reveals that in 1992, significant positive synergies existed between ESs in the northern and northwestern regions, with WY negatively correlated with other services. By 2022, accelerated urbanization has intensified trade-off effects in the southern and eastern regions, leading to significant ecological degradation. This study provides scientific support for the sustainable management and policymaking of watershed ecosystems.